Transfer of ochratoxin A into tea and coffee beverages - Malir, Frantisek; Ostry, Vladimir; Pfohl-Leszkowicz, Annie; Toman, Jakub; Bazin, Ingrid; Roubal, Tomas (Toxins, 2014)
Ochratoxin A (OTA) is nephrotoxic, hepatotoxic, immunotoxic, neurotoxic, reprotoxic, teratogenic, and carcinogenic (group 2B), being characterized by species and sex differences in sensitivity. Despite the fact that OTA is in some aspects a controversial topic, OTA is the most powerful renal carcinogen. The aim of this study was to make a small survey concerning OTA content in black tea, fruit tea, and ground roasted coffee, and to assess OTA transfer into beverages. OTA content was measured using a validated and accredited HPLC-FLD method with a limit of quantification (LOQ) of 0.35 ng/g. The OTA amount ranged from LOQ up to 250 ng/g in black tea and up to 104 ng/g in fruit tea. Black tea and fruit tea, naturally contaminated, were used to prepare tea infusions. The transfer from black tea to the infusion was 34.8% ± 1.3% and from fruit tea 4.1% ± 0.2%. Ground roasted coffee naturally contaminated at 0.92 ng/g was used to prepare seven kinds of coffee beverages. Depending on the type of process used, OTA transfer into coffee ranged from 22.3% to 66.1%. OTA intakes from fruit and black tea or coffee represent a non-negligible human source.
Keywords: káva; Chromatography, High Pressure Liquid; vysokoúčinná kapalinová chromatografie; koncentrace vodíkových iontů; ochratoxiny; čaj; kontaminace potravin; Hydrogen-Ion Concentration; Fruit; ovoce; Coffee; Ochratoxins; Tea; Food Microbiology; Food Contamination; potravinářská mikrobiologie